Acidic polysaccharides from Psidium cattleianum (Araçá) - Vriesmann,Lúcia Cristina (2009)
The aim of this work was to study the acidic polysaccharides of Psidium cattleianum. Pectic fractions were obtained by successive extractions with water, EDTA and sodium carbonate (4 and 25ºC). Monosaccharide composition, total carbohydrates, uronic acids and protein contents were determined for each fraction. The yield of water and EDTA-soluble fractions and high content of uronic acid were consistent with the presence of pectins probably arising from the middle lamellae. On the other hand, sodium carbonate-soluble pectins had a higher neutral sugar content, indicating highly branched polysaccharides in these fractions, consistent with pectins from cell wall.